Novel Ehrlichia and Hepatozoon genotypes in white-eared opossums (Didelphis albiventris) and associated ticks from Brazil - André, Marcos Rogério [UNESP]; Calchi, Ana Cláudia [UNESP]; Perles, Livia [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; Uccella, Lucas [UNESP]; Lemes, Jhessye Rafaela Batista [UNESP]; Nantes, Wesley Arruda Gimenes; Santos, Filipe Martins; Porfírio, Grasiela Edith de Oliveira; Barros-Battesti, Darci Moraes [UNESP]; Herrera, Heitor Miraglia; Machado, Rosangela Zacarias [UNESP] (Elsevier, 2022)
White-eared opossums (Didelphis albiventris) are well adapted to anthropized areas. The increased contact with domestic animals and humans mediates the transmission of arthropod-borne pathogens. Despite the worldwide occurrence of tick-borne Anaplasmataceae and Hepatozoidae species in a variety of vertebrates, few studies reported serological evidence or molecular detection of theses agentes in marsupials. Up to now, while Ehrlichia/Anaplasma spp. have only been detected in marsupials from Brazil, Hepatozoon spp. have been reported in marsupials from Chile, Australia and Brazil. The present work aimed to investigate, using molecular techniques and blood smear analysis, the presence of Ehrlichia spp., Anaplasma spp., and Hepatozoon sp. in the blood and ticks collected from D. albiventris in urban forest fragments from midwestern Brazil. Between May and December 2017, 43 D. albiventris (27 males and 16 females) were captured for blood and tick collection in the city of Campo Grande, state of Mato Grosso do Sul, midwestern Brazil. Ticks (46 Amblyomma dubitatum nymphs and 24 Amblyomma spp. larvae) were collected from 14 out 43 (32.5%) of the white-eared opossums. Panoptic-stained blood smears were performed using peripheral blood (tail tip) of the captured opossums. DNA extracted from blood and tick samples were subjected to PCR/qPCR assays for Anaplasmataceae agents (rrs, gltA, groEL, sodB, and dsb genes, and 23S-5S intergenic region) and Hepatozoon spp. (18S rRNA gene), followed by Sanger sequencing, BLASTn and phylogenetic analyses. An inclusion resembling Ehrlichia morulae was found in a white-eared opossum's monocyte from a blood smear stained with Panoptic. Five (11.63% [5/43]) white-eared opossums’ blood samples and 7 (25% [7/28]) tick samples (2 pools of Amblyomma spp. larvae and 5 pools of A. dubitatum nymphs) were positive for Anaplasmataceae via a PCR assay targeting the conserved rrs gene. Phylogenetic analysis based on the rrs gene positioned three sequences obtained from opossums and ticks together as a subclade within the Ehrlichia canis clade. However, all samples were negative in a qPCR assay specific for E. canis based on the dsb gene. Phylogenetic analyses positioned the gltA and 23S-5S ITS sequences obtained from opossums’ blood samples in a separate clade from the other validated Ehrlichia species. One (2.3% [1/43]) opossum blood sample was positive for the 18S rRNA gene of Hepatozoon sp. The phylogenetic analysis positioned the Hepatozoon sp. sequence obtained from a D. albiventris specimen in a clade with a sequence previously detected in a black storm petrel (Oceanodroma melania) from Mexico. All the other sequences of Hepatozoon sp. previously detected in marsupials from Brazil were positioned in a separated clade. The present work showed the occurrence of putative novel genotypes of Ehrlichia sp. and Hepatozoon sp. in white-eared opossums and associated A. dubitatum ticks from midwestern Brazil.
Keywords: Ehrlichia spp., Hepatozoon spp., marsupials; Tick-borne agents